2012
DOI: 10.1002/jmv.23407
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in IL28B affects viral evolution of hepatitis C quasispecies after pegylated interferon and ribavirin therapy

Abstract: Interleukin-28B (IL28B) polymorphisms are associated with viral response to peginterferon and ribavirin in chronic hepatitis C (HCV). Their recognition represents a breakthrough in the understanding of the role of the host in viral eradication. How these polymorphisms determine viral eradication is unknown. The IL-28B variants are hypothesized to have a differential impact on HCV quasispecies evolution during treatment with pegylated interferon and ribavirin. In this study, HCV RNA levels were measured at earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Since 2009, several single nucleotide polymorphisms (SNP) have been reported near the interleukin 28B gene (IL-28B) that influence response to dual antiviral therapy [89][90][91][92][93][94] . However, it was not until 2011 that the relationship between HCV quasispecies diversity and the host IL-28B genotype was investigated [95] .…”
Section: Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2009, several single nucleotide polymorphisms (SNP) have been reported near the interleukin 28B gene (IL-28B) that influence response to dual antiviral therapy [89][90][91][92][93][94] . However, it was not until 2011 that the relationship between HCV quasispecies diversity and the host IL-28B genotype was investigated [95] .…”
Section: Dynamicsmentioning
confidence: 99%
“…These results might indicate that the IL-28B genotype influences viral evolution and disease outcome in addition to the behaviour of the innate immune system. More recently, Yuan et al [94] (2012) found that, despite exhibiting similar baseline viral loads, more chronically-infected patients with the rs12979860-CC polymorphism had amino acid substitutions in NS5A compared to non-CC patients. This result suggests that patients with the CC genotype undergo early viral evolution probably as a consequence of the selective pressure exerted by the use of interferon at the beginning of treatment.…”
Section: Dynamicsmentioning
confidence: 99%
“…Blood samples were collected from participants at baseline and hours 4, 8, 12, 18, 24, 28, 32, 48; days 3, 4, 7, 9, 11; and weeks 2, 3, 4, 6, 8, 12, 16, 20, 24, 30, 36, 42, 48 and 60 after the start of treatment. IL28B gene polymorphism was determined at baseline by sequence analysis of genomic DNA extracted from blood samples as previously described . HCV viral loads at each time point were measured by VERSANT ® HCV RNA 3.0 assay with detection limit of 43 copies/mL (Siemens Medical Solutions Diagnostics, Tarrytown, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Others have suggested the participation of the IL-28B genotype in the evolution of HCV (24).Whether the host IL-28B genotype is responsible for the rapid sequence divergence observed among these patients requires further research. One of the limitations of our study was the lack of CC IL-28B genotype HCV-infected subjects.…”
mentioning
confidence: 99%